KONSEPTUALISASI "KURIKULUM CINTA": KOMPARASI PERSPEKTIF KH. AHMAD DAHLAN DAN KI HAJAR DEWANTARA - Hermanto, Hermanto; Mujahidah, Nelly (PENA KREATIF : JURNAL PENDIDIKAN, 2026)
Education in Indonesia is often trapped in cognitive formalities and neglects the aspect of affection or "heart". This study aims to explore and compare the concept of education based on compassion or "Curriculum of Love" from two national education figures, KH. Ahmad Dahlan and Ki Hajar Dewantara. The method used in this research is library research with a philosophical-comparative approach to primary and secondary works relevant to the thoughts of both figures. The results show that Ki Hajar Dewantara formulated the concept of love through the "Among System" (Asah, Asih, Asuh) which breathes humanist-nationalist, while KH. Ahmad Dahlan manifested love through Al-Ma'un theology and compassion based on religious-social values. Although departing from different foundations (nationalist vs. religious), the two figures meet at a meeting point, namely placing educators not as rulers who punish, but as guardians who love. The synthesis of this thought is relevant to be applied as a foundation for strengthening character education in the modern era.